Physiological and behavioural ecology of the Cape cormorant Phalacrocorax capensis (Sparrman), 1788 - Berry, H. H.(Hermanus Human) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1975.